Host–Pathogen–Vector Continuum in a Changing Landscape: Potential Transmission Pathways for Bartonella in a Small Mammal Community - B. R. Ansil; Ashwin Viswanathan; Vivek Ramachandran; H. M. Yeshwanth; Avirup Sanyal; Uma Ramakrishnan (Ecology and Evolution, 2025)
ABSTRACT Bacterial infections account for a large proportion of zoonoses. Our current understanding of zoonotic spillover, however, is largely based on studies from viral systems. Small mammals such as rodents and their ectoparasites present a unique system for studying several bacterial pathogens and mapping their spillover pathways. Using Bartonella spp. (a Gram‐negative bacteria) as a model system within a rainforest human‐use landscape, we investigated (1) ecological correlates of Bartonella prevalence in small mammal hosts and (2) evolutionary relationships between Bartonella spp. and various hosts and ectoparasites to gain insight into pathogen movement pathways within ecological communities. We detected Bartonella in five out of eight small mammal species and in 86 (40.56%) out of 212 individuals, but prevalence varied widely among species (0%–75.8%). Seven of the ten ectoparasite species found on these small mammals were positive for Bartonella. Interestingly, while Bartonella genotypes (15) in small mammals were host‐specific, ectoparasites had nonspecific associations, suggesting the possibility for vector‐mediated cross‐species transmission. We also found that Bartonella prevalence in hosts was positively correlated with their aggregated ectoparasite loads, further emphasizing the crucial role that ectoparasites may play in these transmission pathways. Our cophylogenetic analysis and ancestral trait (host) reconstruction revealed incongruence between small mammal and Bartonella phylogenies, indicating historic host shifts and validating the potential for contemporary spillover events. We found that small mammal hosts in this fragmented landscape often move across habitat boundaries, creating a transmission pathway (via shared ectoparasites) to novel hosts, which may include synanthropic species like Rattus rattus. Our results highlight the necessity to disentangle the complex relationship among hosts, ectoparasites, and bacterial pathogens to understand the implications of undetected spillover events.